Pharmacy Leaders' Advice to Students Pursuing Leadership: A Qualitative Study - Radhika Devraj; Ashley Castleberry; Nancy Alvarez; Adam Persky; Therese Poirier (University of Minnesota Libraries Publishing, 2023)
Introduction: Leadership development is important both from a curricular standpoint and for continued advancement of the profession. Advice from current leaders in the profession may serve as a powerful motivator to students desiring to be leaders. The purpose of this qualitative study was to provide advice from experienced pharmacy leaders. Methods: Fifty-four pharmacy leaders were identified based on pre-determined, specific criteria and by using a snowball sampling method. Interviews with leaders were conducted via Zoom to learn about their leadership journey, their legacy, and advice they would give students. The interviews were transcribed, de-identified and analyzed using the inductive, modified constant comparison approach for open and axial coding. Advice themes were compared by gender and generational category. Results: The majority of the interviewees were male (69%), belonged to the Baby Boomer Generation (1946-1964, 59.3%), and held leadership positions in education (78%) and health systems (48%). Thirty-seven leadership advice themes were present. The topmost advice to students was to keep an open mind (35%) and to get involved in organizations (32%). Pieces of advice shared by both men and women leaders included:  being open minded, getting involved in organizations, taking initiative, trying new or difficult things, and finding your passion. Keeping an open mind, and taking initiative were common across the three generations. Conclusion: Pharmacy leaders have insightful information for students aspiring to be future leaders. Leadership advice was similar by gender and generational category. Students would benefit in developing their leadership based on advice from the lived experience of pharmacy leaders. Future studies could examine students' perspectives on leadership advice.